The nature of motivational factors related to achievement of English as a Foreign Language in Turkey. - Ozkut, Iffet E. (University of Ottawa (Canada), 1991)
The motivational dimension of second/foreign language learning has received considerable emphasis in the literature as a means of better predicting language achievement and understanding the factors that influence language learning. The present study is an attempt to analyze the nature of orientations towards learning English as a foreign language, and to test whether they are related to other constructs, such as motivation and proficiency, in a context not hitherto explored. To this end, four instruments were administered to a random sample of approximately 200 male and female university students in Humanities and Science in Turkey. These students were enrolled in intensive English language programs at the time of testing. The instruments consisted of (1) a cloze test to measure language proficiency; (2) a questionnaire to assess Ss' reasons for studying L$\sb2$; (3) a Motivational Intensity Scale to assess the students' effort in studying L$\sb2$; and (4) a Desire to Learn L$\sb2$ Scale to assess the degree to which Ss want to learn L$\sb2$. The data was subjected to factor analyses and seven orientations to learn English were found to be common to all groups studied. Results of correlational analyses showed that there was a relationship between motivation and proficiency for females in the sample. There was no significant relationship between proficiency and any of the seven orientations for either sex. Results based on MANOVA to determine the main effects for sex and field of study revealed significant effects for sex but not for field. A second factor analysis was done to assess the relationships between the seven orientations and motivation and proficiency for males and females separately. Four factors for females and three factors for males were obtained. A detailed description was given of the cultural, historical and educational context where English as a Foreign Language (EFL) takes place, where there is almost no contact with native speakers of English outside the classroom. This study contributes to those already conducted to test the most recent models of language learning in contexts both outside and within North America.
Keywords: Education, Language and Literature.